Some Aspects Of The Biology And Population Dynamics Of The Dominant Fish Species In Kedungombo Reservoir, Central Java, Indonesia - Kartaminhardja, Endi Setiadi (1993)

(untitled)
The study was aimed to investigate some aspects of the biology and population dynamics of dominant fish species, namely Oreochromis mossambicus (Peter) , Puntius gonionotus (Bleeker) , Puntius bramoides (Cuvier & Valenciennes) , Mysracoleucus marginatus (Cuvier & Valenciennes) , and Channa striatus Bloch in the Kedungombo Reservoir, Central Java, Indonesia. Gillnet sampling in six sub-fishing areas of the reservoir once a month for a 12 month period and catch assessment survey (CAS) at three fish landing sites were carried out. Length-based methods for fish population study were adopted. Results of the study showed that the dominant species were distributed all over the reservoir, except C. striatus which were distributed in a restricted area. The riverine species were concentrated in the upper portion of the reservoir. The species richness and diversity of the fish community were high in the upper portion of the reservoir. Based on the values of the index of preponderance, O. mossambicus and M. marginatus were classified as planktivores; P. gonionotus and P. bramoides as herbivores; and C. striatus as a carnivore. Food competition occurred between O. mossambicus and M. marginatus, and between P. gonionotus and P. bramoides. However, the food competition among other species was considered low. O. mossambicus reproduced at intervals of about three months and their reproduction occurred extensively during high water level . Reproduction of P. gonionotus, P. bramoides and M. marginatus started from December until March when the water level of the reservoir began to rise. In C. striatus reproduction occurred during high water level . Fecundity of O. mossambicus, P. gonionotus, P. bramoides, M. marginatus and C. striatus were between 178- 1,574; 25 ,980-86,916; 42 ,454-99 , 659; 4 , 702- 15 , 681 ; and 2 , 585- 12 , 880, respectively . The fecundity was highly correlated with total length , body weight, and gonad weight and it increased with the increase in total length , body weight and gonad weight.